THE EFFECT OF BIOBOOSTADDITION WITH DIFFERENT DOSES ON MAINTENANCE MEDIA WITH BIOFLOC SYSTEM ON GROWTH AND SURVIVAL RATE OF FISH SEED BAUNG (Hemibagrus nemurus) - Satriani, Esti; Pamukas, Niken Ayu; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of the study was to determine the best doses of bioboost in the biofloc system for increasing the growth and survival rate of fish seed baung(Hemibagrus nemurus).This research was conducted for 50 days from April 2 to May22 2019, in the Technical Service Unit (UPT) Hatchery and Experimental Pond of the Faculty of Fisheries and Marine University of Riau.This research was using the experimental method by completely random design (RAL) with 4 levels of treatment three replications.The treatments applied P1 = Giving bioboost 5 ml/m3, P2 = Giving bioboost 10 ml/m3, P3 = Giving bioboost 15 ml/m3, P4 = Giving bioboost 20 ml/m3. The results showed that the addition of different bioboost doses showed a significant effect (P <0,05) on absolute weight growth (Wm), absolute length growth (Lm), specific growth rate (LPS), feed efficiency (EP), feed conversion ratio (FCR) and no significant effect (P> 0,05) on survival rate (SR) of baung fish. The best treatment is giving bioboost 15 ml/m3(P3) which produces absolute weight growth of 6,01 g, absolute length growth of 5,19 cm, the specific growth rate of 1,89%, feed efficiency of 104,09%, feed conversion ratio 0,98 and survival rate 100% . Keywords:Doses,Bioboost, Biofloc, Growth,Hemibagrus nemurus.